The Influence of Herding, Anchoring, Disposition, Personal Income, and Financial Literacy on Generation Z's Investment Decision Making in Surabaya City - Falah, Fahmi Faiqotul; Asandimitra, Nadia (Technium Social Sciences Journal, 2023)
This study examines the investment decisions of Generation Z in the city of Surabaya and analyzes the relationship between herding, anchoring, disposition, personal income, and financial literacy. The object of this research is Gen Z in the city of Surabaya, and the data collection technique uses a purposive sampling technique. The total number of respondents obtained was 232 people by distributing questionnaires online. This research concludes on causality and utilizes Structural Equation Modeling analysis techniques on AMOS version 24 software. The results of this study indicate that herding and disposition have a significant positive effect on investment decisions, while anchoring, personal income, and financial literacy have no effect on investment decisions. This study can serve as a useful reference for various parties, especially investors who should always act and behave wisely when making decisions in the capital market.